Pengembangan Potensi Pariwisata Kampung Wisata Haji Dorani dengan Peningkatan Brand Awareness - Zahra Azhar Shafira Puspita Hakim; Anggraini Sukmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Malaysia is a multicultural country. This indicates the diversity of human resources. This proper management of human resources can make Malaysia's tourist attraction attractive. Especially in Sungai Haji Dorani Village, Sungai Besar. This study aims to analyze the management of tourism brand awareness in Kampung Sungai Haji Dorani, Selangor. Data analysis methods used include analysis of the distribution of Kuala Selangor residents based on ethnicity and the way they interact. Data collection techniques are carried out by means of observation, interviews and recording. Secondary data obtained by analysis and recording of literature. The existence of diversity makes people more heterogeneous and can exchange ideas. Tourism is an activity that affects the economic conditions of the community. Malaysia occupies the 29th position out of 140 countries in the field of tourism. This country develops tourism with various models. One of them developed in Kuala Selangor is a homestay program in the Sungai Haji Dorani Kampung area. The nuances and daily activities of the residents offered are the main attraction of tourism there.